2023
DOI: 10.1177/23969873231209819
|View full text |Cite
|
Sign up to set email alerts
|

Early and recurrent cerebral vasospasms after aneurysmal subarachnoid hemorrhage: The impact of age

Bogdana Tokareva,
Lukas Meyer,
Christian Heitkamp
et al.

Abstract: Introduction: Cerebral vasospasms remain a strong predictor of poor outcome after aneurysmal SAH. The aim of this study was to describe the time course of relevant vasospasms after aneurysmal SAH and to determine the variables associated with early-onset or prolonged and recurrent vasospasms. Patients and methods: We conducted a retrospective, single-center study of consecutive adult patients with aneurysmal SAH admitted between 2016 and 2022 at our tertiary stroke center. Relevant vasospasms, defined as vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…One-third of the patients usually die at the time, and the other one-third develop permanent disability, which seriously affects the patient's quality of life. [1][2][3] Studies 4,5 have found that early brain injury (EBI) is one of the pivotal factors causing this outcome after SAH. EBI involves a variety of physiological disorders, including neuroinflammatory injury, blood-brain barrier disruption, nerve cell apoptosis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…One-third of the patients usually die at the time, and the other one-third develop permanent disability, which seriously affects the patient's quality of life. [1][2][3] Studies 4,5 have found that early brain injury (EBI) is one of the pivotal factors causing this outcome after SAH. EBI involves a variety of physiological disorders, including neuroinflammatory injury, blood-brain barrier disruption, nerve cell apoptosis, etc.…”
Section: Introductionmentioning
confidence: 99%